Analisis Kelayakan Investasi Pembelian Mesin CNC Bubut Mazak 150s untuk Meningkatkan Kapasitas Produksi dengan Teknik Capital Budgeting (Studi Kasus pada CV. Gaya Indah) - Afifatun Nik'mah; Aditya Maharani; Dian Asa Utari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
CV. Gaya Indah (CV. GI) is a company engaged in the field of machining services. One of the products being produced is bush kora. Bush kora is a spare part of a motor vehicle that functions as a protector/house for bearings. In 2021 the number of requests for bush kora products increased rapidly to increase production capacity the company's want to change the production flow from 1 machine to 2 machines, but the number of machines in the company was not sufficient so the Company plans to invest in Mazak Quick Smart 150s CNC Lathe Machine by considering technical/operational aspects and financial aspects. The results of the analysis obtained in the technical/operational aspect is that the production capacity can meet the eligibility requirements, that is demand < production capacity. In the financial aspect, the feasibility assessment criteria using NPV (Net Present Value) has a positive value of Rp. 50.694.290,-, the percentage of IRR (Internal Rate of Return) is 9,138% and is greater than the discount factor specified, that is 6,678% , and the payback period shows that the time required to return the invested investment is 5 months 16 days faster than the project contract period, which is 1 year, so from the results of the analysis using the capital budgeting technique, it is stated that the investment plan is feasible to implement.